The Fallacy of Using the National Assessment Program-Literacy and Numeracy (NAPLAN) Data to Identify Australian High-Potential Gifted Students - Michelle Ronksley-Pavia (MDPI AG, 2023)
In Australia, gifted or talented students are defined according to the widely accepted model proposed by Gagné, where giftedness is understood as potential, and talent is shown through competencies (or achievements); in this definition there is a clear differentiation between the two constructs. Most Australian education jurisdictions espouse Gagné's definitions and use a variety of mechanisms for identifying gifted and talented students-a commonly used identification practice is the results from the Australian National Assessment Program-Literacy and Numeracy (NAPLAN) test. This article sets out to explore the fallacy of using the NAPLAN results to identify giftedness in high-potential (gifted) students in Australia, outlining key reasons why the NAPLAN is unsuitable as an identification instrument for giftedness. Moreover, it explores the erroneous use of the NAPLAN as an identification tool for giftedness when it was never designed, validated, or intended as such an instrument.